Fabrication of coupled GaAs quantum dots and their optical properties - Kim, J.S.; Song, J.D.; Byeon, C.C.; Kang, H.; Jeong, M.S.; Cho, N.K.; Park, S.J.; Choi, W.J.; Lee, J.I.; Kim, J.S.; Leem, J.-Y.; Yim, S.-Y.; et al. (2009)
The coupled GaAs quantum dot molecules (QDMs), which were laterally coupled along the [110] direction, were formed by droplet epitaxy. The optical properties of QDMs were investigated by femtosecond laser excited photoluminescence (PL) measurement. When the laser polarization is parallel to [110] direction on the QDMs, the main PL peak is red-shifted by 55 meV from the PL peak measured with the laser polarization parallel to [110] direction. By changing the excitation power, we found that the emission wavelength of the QDMs was strongly depending on the excitation laser polarization. From this result, we carefully suggested that the confined states in QDMs could be tuned by optical field. ？ 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.